2021
DOI: 10.1029/2021gl092438
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Engineered Diversions and Natural Avulsions on Delta‐Lobe Stability

Abstract: Reduced sediment supply and rising sea levels are driving land submergence on deltas worldwide, motivating engineering practices that divert water and sediment to sustain coastal landforms. However, lobe response following channel abandonment by diversions has not been constrained by field‐scale studies. Herein, avulsion and engineered diversion scenarios are explored for the Huanghe delta (China), where three lobes were abandoned in the last 40 yr. Two lobes were completely cut off by diversions, and one natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The Phase II process and associated degrading evolution of the DF waned following 2000 CE (Figure 5f), which suggested that the DKL is approaching a morphological equilibrium after ∼20-year of evolution. This hypothesis is also supported by previous shoreline studies (e.g., Carlson et al, 2021) which suggested that the rate of 9 (i.e., two sediment gravity flow [SGF]-related units formed a wedge downlap on the middle and lower delta front with many submarine channels at/near the landward termini of the SGF units) are also observable at other regions of our focused area, suggesting a widespread phenomenon. In panel (a), the SGF-related units off Diaokou lobe also experienced postdepositional sediment loss.…”
Section: Discussionsupporting
confidence: 91%
“…The Phase II process and associated degrading evolution of the DF waned following 2000 CE (Figure 5f), which suggested that the DKL is approaching a morphological equilibrium after ∼20-year of evolution. This hypothesis is also supported by previous shoreline studies (e.g., Carlson et al, 2021) which suggested that the rate of 9 (i.e., two sediment gravity flow [SGF]-related units formed a wedge downlap on the middle and lower delta front with many submarine channels at/near the landward termini of the SGF units) are also observable at other regions of our focused area, suggesting a widespread phenomenon. In panel (a), the SGF-related units off Diaokou lobe also experienced postdepositional sediment loss.…”
Section: Discussionsupporting
confidence: 91%
“…More efforts, resources, and engineered diversions will be necessary to prevent avulsion as channels aggrade more quickly and farther upstream during sea‐level rise (Kim et al., 2009; Moodie & Nittrouer, 2021; Temmerman & Kirwan, 2015). Modified deltas may also be at risk of unexpected new avulsion sites if levee and dam infrastructure has sufficiently altered backwater effects and aggradation patterns since the last avulsion (Carlson et al., 2021; Chadwick & Lamb, 2021; Moodie & Nittrouer, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…At present, shorelines of many deltas in the world are experiencing land loss due to declining sediment supply and accelerating rates of sea‐level rise (Blum & Roberts, 2009; Syvitski & Saito, 2007). Because large river deltas are densely populated and are transportation hubs and industrial and commercial centers, artificial bifurcation have been implemented, or are being considered, as a viable engineering tool to divert flow and sediment for combating coastal land loss, especially on those densely populated deltas such as the Yellow River delta (Carlson et al, 2021; Syvitski & Saito, 2007) and the Mississippi River Delta (Shaw et al, 2021; Wang & Xu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of sediment division through artificial bifurcation can be affected by a number of factors, such as channel slope (Iwantoro et al, 2021), friction factor (Edmonds & Slingerland, 2008), Shields number (Bolla Pittaluga et al, 2003), bed sediment sorting (Kleinhans et al, 2008), aspect ratio upstream channel (Bolla Pittaluga et al, 2015), elevation before sediment loss (Carlson et al, 2021), and tidal amplitudes (Ragno et al, 2020). Differences in bed composition between the old channel and the new branch are also relevant, which can affect long-term bifurcation stability.…”
mentioning
confidence: 99%
See 1 more Smart Citation